THE USE INTERACTIVE MULTIMEDIA IN GEOGRAPHY LEARNING TO INCREASE STUDENTS INTEREST IN LEARNING CLASS XI IPS SMA NEGERI 2 MAWASANGKA TENGAH - Lisnawati, Lisnawati (Geographica: Science and Education Journal, 2023)
This study aims to determine the increase in student interest in learning with the use of interactive multimedia in learning geography of students of class XI IPS SMAN 2 Mawasangka Tengah.  The subject of the research is XI IPS class students totaling 20 students. The type of research is classroom action research with research stages consisting of planning, implementation, observation, and reflection.  Data was obtained from a questionnaire of learning interest and an observation sheet of learning activities. The results showed that students' interest in learning increased in each learning cycle implemented.  In cycle 1, the results of the learning interest questionnaire had an average value of 56 which showed that 7 students had low interest in learning, 8 students had moderate interest in learning, and 5 students had high interest.  After the implementation of the 2nd cycle action, students' scores have increased with an average score of 71 which shows 6 students have moderate interest and 14 students have high interest in learning.  Therefore, it can be concluded that the use of interactive multimedia in learning geography can increase the learning interest of students of class XI IPS SMA Negeri 2 Mawasangka Tengah.